Produção de juvenis masculinizados ou não, de tilápia híbrida de vermelha da Flórida e Oreochromis niloticus, com duas dietas comerciais - Rossi, Naiara Portolani [UNESP] (Universidade Estadual Paulista (Unesp), 2022)
In tilapia production in Brazil, the hormone 17-α-methyltestosterone is used during larviculture, however, the use of diets with this hormone can negatively impact the health of fish. The objective of this work was to evaluate the performance, survival, uniformity and partial net income in the production of red tilapia larvae, masculinized or not, submitted to two commercial diets of different protein levels, using 3,600 thousand tilapia larvae distributed in 24 polyethylene boxes with a useful volume of 150 liters at a density of 150 larvae/box, under constant aeration, in a continuous water system. The design was completely randomized, with six treatments and four replications in a factorial scheme (3x2). The experimental period was 30 days, and three main factors were evaluated: masculinization by hormone (60 mg 17-α-methyltestosterone/kg of diet) (MH), masculinization by temperature (MT) and non-masculinization of larvae (NM); and two secondary factors: commercial mash feed (COM) with crude protein (CP) level of 52% and ecological feed (ECO) with CP level of 44%. The fish performance parameters were measured. The results of the studied variables were submitted to analysis of variance with 5% significance using the R version 4.0.2 program. There were no significant differences in the masculinization effect and diet effect on larval performance, with the exception of the coefficient of variation of the final weight, in which the ecological diet affected positively, making the batch more homogeneous. In this way, it is possible to reduce the crude protein in the diet by 8% without compromising the main performance variables regardless of the masculinization method. In the economic analysis, the results found show that the NM treatment, regardless of the protein level, has the lowest cost and also has the highest partial net income.

Na produção de tilápia no Brasil, o hormônio 17-α-metiltestosterona é utilizado durante a larvicultura, porém, o uso de dietas com esse hormônio pode causar impactos negativos na saúde dos peixes. O objetivo deste trabalho foi avaliar o desempenho, sobrevivência, uniformidade e a receita líquida parcial na produção de larvas de tilápia vermelha masculinizadas ou não, submetidos a duas dietas comerciais de níveis proteicos, utilizando 3.600 mil larvas de tilápia, distribuídas em 24 caixas de polietileno com volume útil de 150 litros em densidade de 150 larvas/caixa, sob aeração constante, em sistema contínuo de água. O delineamento foi inteiramente casualizado, com seis tratamentos e quatro repetições em esquema de fatorial (3x2). O período experimental foi de 30 dias, sendo avaliados três fatores principais: masculinização por hormônio (60 mg de 17-α-metiltestosterona/kg de dieta) (MH), masculinização por temperatura (MT) e a não masculinização das larvas (NM); e dois fatores secundários: ração comercial farelada (COM) com nível de proteína bruta (PB) de 52% e ração ecológica (ECO) com nível de PB de 44%. Foram mensurados os parâmetros de desempenho dos peixes. Os resultados das variáveis estudadas foram submetidos à análise de análise de variância com 5% de significância pelo programa R versão 4.0.2. Não houve diferenças significativas do efeito masculinização e efeito dieta no desempenho das larvas, com exceção do coeficiente de variação do peso final do lote, no qual a dieta ecológica afetou positivamente, tornando o lote mais homogêneo. Desse modo, é possível reduzir a proteína bruta da dieta em 8% sem comprometer as principais variáveis de desempenho independentemente do método de masculinização. Já na análise econômica, os resultados encontrados mostram que o tratamento NM, independente no nível proteico, é o de menor custo e também apresenta maior receita líquida parcial.
Production of juveniles, masculinized or not, of hybrid Florida red tilapia and Oreochromis niloticus, with two commercial diets
Keywords: Tilapia (Peixe); Peixe Larva vitelínica; Dieta